THE STUDY OF LACUNAR UNITS IN BILINGUAL LEARNERS’ DICTIONARIES BASED ON DISCOURSE ANALYSIS - Tog‘aymurodova , Sevara (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This thesis examines the representation of lacunar lexical units in bilingual learners’ dictionaries through the lens of discourse analysis. Lacunar units are interpreted as lexical items that exist in one language but lack a direct or complete equivalent in another language, and they constitute one of the significant challenges in bilingual lexicography as well as in intercultural communication.